Evaluation of The Dimensions and Thickness of The Adi Soemarmo Surakarta Airport Apron Pavement Using The FAA (Federal Aviation Administration) Method - Andika Andika; Latif Budi Suparma; Suryo Hapsoro Tri Utomo (Eduvest - Journal of Universal Studies, 2023)
Air transportation is the most recent mode of transportation among other modes and only emerged and developed in the 20th century. World Wars I and II gave a great impetus to the development of air transport in almost every country in the world. To make it easier to conduct this research, it is necessary to collect data related to "Evaluation of the Dimensions and Thickness of the Adi Soemarmo Surakarta Airport Apron Pavement Using the FAA (Federal Aviation Administration) Method". Data on air traffic movements is needed in performing the role or designing the pavement thickness of airport airside facilities. Data on aircraft movements is needed in forecasting the growth rate of aircraft at airports. It takes at least 10 years or at least the last 5 years to forecast the movement of the aircraft. The results of the calculation of apron dimensions were obtained by 560 m × 135 m while the dimensional conditions of the existing apron were 420 m × 135 m. Based on the results of these calculations, it is necessary to increase the apron length by 140 m, while for the width of the apron there is no need to widen so that the apron is able to serve aircraft traffic optimally for the next 20 years at Adi Soemarmo Surakarta Airport